2014
DOI: 10.1101/gr.163659.113
|View full text |Cite
|
Sign up to set email alerts
|

Somatic retrotransposition in human cancer revealed by whole-genome and exome sequencing

Abstract: Retrotransposons constitute a major source of genetic variation, and somatic retrotransposon insertions have been reported in cancer. Here, we applied TranspoSeq, a computational framework that identifies retrotransposon insertions from sequencing data, to whole genomes from 200 tumor/normal pairs across 11 tumor types as part of The Cancer Genome Atlas (TCGA) Pan-Cancer Project. In addition to novel germline polymorphisms, we find 810 somatic retrotransposon insertions primarily in lung squamous, head and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
226
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(253 citation statements)
references
References 69 publications
(97 reference statements)
18
226
2
Order By: Relevance
“…These studies have also demonstrated that several types of epithelial cancers acquire somatic insertions of LINE-1 as they develop (15,19,24,26). Recent projects mining whole-genome sequencing data have extended our understanding of the scope of heritable LINE-1 insertions (20,21,47) and somatic retrotransposition (22,23,48) greatly.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have also demonstrated that several types of epithelial cancers acquire somatic insertions of LINE-1 as they develop (15,19,24,26). Recent projects mining whole-genome sequencing data have extended our understanding of the scope of heritable LINE-1 insertions (20,21,47) and somatic retrotransposition (22,23,48) greatly.…”
Section: Discussionmentioning
confidence: 99%
“…The precise role of ST18 in the development of hepatocellular carcinoma is unknown, and thus it is unclear whether this L1 insertion might have influenced tumor initiation, or instead, later stages of tumorigenesis. Another strong example of a potential L1 driver mutation was identified in the sixth exon of the PTEN tumor suppressor gene in a case of uterine corpus endometrial carcinoma (Helman et al 2014). Because this insertion disrupted a coding exon, the tumor likely had lower levels of PTEN activity.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing has revolutionized somatic L1 discovery over the past 6 yr, leading to the identification of thousands of somatic L1 insertions in several types of human epithelial cancers (Iskow et al 2010;Lee et al 2012;Solyom et al 2012;Shukla et al 2013;Helman et al 2014;Tubio et al 2014;Doucet-O'Hare et al 2015;Ewing et al 2015;Rodic et al 2015). The fact that L1 mobilization occurs frequently in human tumors raises the possibility that somatic L1 insertions could act as driver mutations during tumor initiation, progression, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations